Rampogan Macan: Simbolisme Perlawanan terhadap Kolonial dalam Perayaan Hari Besar Islam (1890-1912) - Karimah, Laila (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This study discusses aboutÂ Rampogan Macan shows conducted in Blitar in 1890-1912. This show is thought as one of the causes of the extinction of Javanese tiger which still causes a debate among the communities. Based on the further studies of some relevant sources of history,Â there is a new perspective of symbolism of this show. The first thing comes in mind when hearing about this show is tiger massacre. HoweverÂ this show also has religiosity values andÂ symbols of peopleâ€™s resistance to colonialism. Symbolizing the tiger as a glorified figure is not applied in this Rampogan Macan show. This is because the main goal of this show is to defeat the tiger which is an enemy representation.Â This study used historical research method with four stages including heuristic, verification of historical sources, interpretation, and hystorigraphy. The results show: first, the origin of Rampogan Macan in Blitar because the pakoso assigned to share they hold show on their area. Second, rampogan tiger as a form of popular resistance against colonial ruler .Third, the impact of the show is a reduction in population Java tigers. Keywords: Rampogan Macan Blitar, Symbolism, Islamic Celebration